Hubungan Kondisi Kerja, Kepuasan Kerja, dan Prestasi Kerja Pekerja Konstruksi di Jakarta - Bimmo Dwi Baskoro; Osrita Hapsara; Sri Mulyono (Universitas Batanghari, 2021)
This study analyses the effect of work on job performance with job satisfaction as a mediating variable. A total of 210 respondents representing construction companies in Jakarta were involved in this study. PLS-SEM (Partial Least Square - Structural Equation Modeling) was used to test the research model. Working conditions do not have a significant effect on work performance. However, it is known that job satisfaction mediates the relationship between working conditions and work performance. This study has several limitations so that the results of the study cannot be generalized to other sectors.